Стовбихва: виселене село в джерелах усної історії - Дмитренко, А. (Краєзнавство, 2019)
У статті висвітлюються основні події з життя села Стобихва Камінь-Каширського району Волинської області та його мешканців у ХХ столітті. Завдання дослідження – проаналізувати фактори, які спричинили трансформацію Стобихви від містечка до вмираючого населеного пункту із застосуванням методу усної історії – фіксування суб'єктивних знань конкретних людей шляхом інтерв'ювання; розшифровування, аналізу і узагальнення зібраних свідчень. Наводяться польові матеріали, що ілюструють основні положення статті. З'ясовано основні причини руйнування села Стобихва у ХХ столітті. Перша – Стохідська військова операція часів Першої світової війни в результаті якої мешканці села були евакуйовані. По закінченні війни стобихівчани повернулися і відбудували село. Друга причина – розбудова Поворського полігону, розміщеного поруч із Стобихвою, що привело до виселення її мешканців у Бессарабію у 1940 році. В період голоду 1946–1947 рр. значна частина стобихівських «бессарабців» повернулась до знищеного села. Третє виселення почалося з 1951 року, коли стобихівчан переселяли у сусідні села та міста і заборонили будівництво нових жител. Залишилась лише невелика кількість мешканців, які до кінця 1980-х років жили без дороги і електрики. Подальшого і більш конкретного вивчення потребують усі сторінки історії села ХХ століття, особливо періоду Другої світової війни та перших повоєнних років і протистояння в середовищі стобихівців. Доцільно з'ясувати географію розселення мешканців Стобихви, виселених у 1940–1950-х рр. Доцільне вивчення звичаєво-обрядової культури. Зібрані, проаналізовані та викладені у статті матеріали сприятимуть вивченню місцевої історії, збереженню та популяризації історичної та культурної спадщини, формуванню туристичних маршрутів. The article covers the main events of the life of the village of Stobyhva in Kamin-Kashirsky district of Volyn region and its inhabitants in the twentieth century. The task of the study is to analyze the factors that caused the transformation of Stobyhva from the town to the dying settlement using the spoken history method - fixing the subjective knowledge of specific people through interviewing; decoding, analyzing and summarizing the collected evidence. Field materials are provided illustrating the main items of the article. The main causes of the destruction of the village of Stobyhva in the twentieth century were found out. The first was the Stohid military operation from the time of the First World War, as a result of which villagers were evacuated. At the end of the war the inhabitants returned and rebuilt the village. The second reason was the development of the Povorsky landfill located next to Stobyhva, which led to the eviction of its inhabitants in Bessarabia in 1940. During the famine of 1946-1947 a large part of the «Bessarabians» of Stobyhva returned to the destroyed village. The third eviction began in 1951 when the villagers were resettled to the neighboring villages and towns and were forbidden to build new houses. Only a small number of inhabitants, who by the end of the 1980s lived without a road and electricity, remained. Further and more specific study of all pages of the history of the village of the twentieth century is needed, especially the period of the Second World War and the first post-war years and the confrontation between Stobyhva inhabitants. It is reasonable to find out the geography of the settlement of the inhabitants of the village evicted during 1940-1950’s. It is expedient to study the customritual culture. The materials collected, analyzed and described in the article will promote the study of local history, preservation and popularization of historical and cultural heritage, and the formation of tourist routes.